2019
DOI: 10.1038/s41556-019-0345-y
|View full text |Cite
|
Sign up to set email alerts
|

An ARF6–Exportin-5 axis delivers pre-miRNA cargo to tumour microvesicles

Abstract: Tumor-derived microvesicles (TMVs) comprise a class of extracellular vesicles released from tumor cells that are now understood to facilitate communication between the tumor and the surrounding microenvironment. Despite their significance, the regulatory mechanisms governing the trafficking of bioactive cargos to TMVs at the cell surface remain poorly defined. Here we describe a molecular pathway for the delivery of microRNA (miRNA) cargo to nascent TMVs involving the dissociation of a pre-miRNA/Exportin-5 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 69 publications
1
106
0
1
Order By: Relevance
“…The exosome is a disk-shaped membranous vesicle with a diameter 30-100 nm, and carries a parental cell cargo including lipids, metabolites, proteins, nucleic acids (DNA fragments, mRNA, miRNA, etc.) delivers pre-miRNA cargo into tumor microvesicles [26]. These regulatory methods demonstrate the mechanism by which ovarian cancer exosomes obtain their distinct molecular signature from surrounding healthy tissue.…”
Section: Exosome Biogenesismentioning
confidence: 95%
“…The exosome is a disk-shaped membranous vesicle with a diameter 30-100 nm, and carries a parental cell cargo including lipids, metabolites, proteins, nucleic acids (DNA fragments, mRNA, miRNA, etc.) delivers pre-miRNA cargo into tumor microvesicles [26]. These regulatory methods demonstrate the mechanism by which ovarian cancer exosomes obtain their distinct molecular signature from surrounding healthy tissue.…”
Section: Exosome Biogenesismentioning
confidence: 95%
“…There is mounting evidence that exosomes mediate the transfer of mRNAs and microRNAs between cells . Recently, it has been reported that PTEN suppression in brain metastatic tumor cells is epigenetically regulated by microRNAs delivered by astrocyte‐derived exosome promoting intercellular transfer of PTEN‐targeting microRNAs to metastatic tumor cells . Caprin‐1 has been associated with the formation of RNA granules and serves as a regulator of post‐transcriptional and epigenetic expression .…”
Section: Resultsmentioning
confidence: 99%
“…The process that leads to MVs generation starts from the formation of outward buds in specific sites of the membrane, followed by fission and subsequent release of the vesicle into the extracellular space [34,35]. This process involves specific machinery in which ADP-ribosylation factor 6 (ARF6) plays a central role [34,36]. They have multiple biological functions depending on the cell type from which they originate and/or on the cargo content that includes proteins and RNAs, including miRNAs [37].…”
Section: Characteristics Of Extracellular Vesiclesmentioning
confidence: 99%